Desain Penelitian Musik di Era Digital (Sebuah Tinjauan Studi Literatur) - Riyan Hidayatullah (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
This article seeks to investigate various literatures that address the issue of music research methodology, discussed in the case of Indonesia. The main background in writing is a lack of sources on music research methods. Especially in the digital age, when there is an abundance of data. A separate investigation is required into the procedures for conducting research, managing data, and understanding the research methods to be used. This article is a review of the literature that employs the exposition method to present general and specific concepts from previous research. The sources used include the outcomes of debates about art and music research. Music research concepts are discussed and reviewed in reference materials, resulting in a new understanding of the subject. The aim is to expand conceptual ideas about music research paradigms and their relevance in the digital age. The principles of art and music research methodology are addressed. Following that, we'll talk about how to design music research in the digital age. The result suggest, the rapid technological advancements are forcing music researchers to revise how data is collected and validated. Data from the internet is no longer used as a complement, but rather as the primary source of capital for digital-based music research design. The components of research in a coherent and logistical way to find answers to research problems are the focus of music research design in the digital age. Make use of relevant apps and websites, as well as big data.